89.7k views
4 votes
Solve the following equations.
log2(x^2 − 16) − log^2(x − 4) = 1

1 Answer

3 votes

Answer:


x=(4*(2+e))/(e-2)

Explanation:

Let's rewrite the left side keeping in mind the next propierties:


log((1)/(x) )=-log(x)


log(x*y)=log(x)+log(y)

Therefore:


log(2*(x^(2) -16))+log((1)/((x-4)^(2) ))=1\\ log((2*(x^(2) -16))/((x-4)^(2)))=1

Now, cancel logarithms by taking exp of both sides:


e^{log((2*(x^(2) -16))/((x-4)^(2)))} =e^(1) \\(2*(x^(2) -16))/((x-4)^(2))=e

Multiply both sides by
(x-4)^(2) and using distributive propierty:


2x^(2) -32=16e-8ex+ex^(2)

Substract
16e-8ex+ex^(2) from both sides and factoring:


-(x-4)*(-8-4e-2x+ex)=0

Multiply both sides by -1:


(x-4)*(-8-4e-2x+ex)=0

Split into two equations:


x-4=0\hspace{3}or\hspace{3}-8-4e-2x+ex=0

Solving for
x-4=0

Add 4 to both sides:


x=4

Solving for
-8-4e-2x+ex=0

Collect in terms of x and add
4e+8 to both sides:


x(e-2)=4e+8

Divide both sides by e-2:


x=(4*(2+e))/(e-2)

The solutions are:


x=4\hspace{3}or\hspace{3}x=(4*(2+e))/(e-2)

If we evaluate x=4 in the original equation:


log(0)-log(0)=1

This is an absurd because log (x) is undefined for
x\leq 0

If we evaluate
x=(4*(2+e))/(e-2) in the original equation:


log(2*(((4e+8)/(e-2))^2-16))-log(((4e+8)/(e-2)-4)^2)=1

Which is correct, therefore the solution is:


x=(4*(2+e))/(e-2)

User Dylanthepiguy
by
6.8k points